Zina dalam Perspektif Tafsir Al-Qur’an - Talebe, Tamrin (Musawa: Journal for Gender Studies, 2019)
This article explores the interpretation of the verse about adultery in the QS. Al-Isra; 32, QS. Al-Nur; 2 in perspective of the Qur'anic Interpretation. The object of the Qur’anic interpretation in this study is the interpretation of al-Tahrir wa al-Tanwir by Ibn ‘Asyur, Tafsir al-Munir by Wahba al-Zuhaili. The study of the interpretation of the Qur'an has a perspective based on asbab al-nuzul, munasabah and the meaning contained in the verse. The results found in the interpretation of the Qur’an showed that the act of adultery is one of the strongly prohibited acts, the law taxt is a strict law and provides the connotation of disclosure loaded with very adverse effects on perpetrators, families and the wider community. Keywords :adultery and Tafsir